2011
DOI: 10.1590/s0073-47212011000100019
|View full text |Cite
|
Sign up to set email alerts
|

Por que Melipona scutellaris (Hymenoptera, Apidae) forrageia sob alta umidade relativa do ar?

Abstract: ABSTRACT. Why do the stingless bee Melipona scutellaris (Hymenoptera, Apidae) forage at high relative air humidity? There are evidences that air temperature and relative humidity exerts influence on the flight activity of the social stingless bees (Meliponini). Particularly, the relatively large species of Melipona Illiger, 1806 would present variation in daily foraging activity very close to variation in relative humidity. In this study, we argue that the relative humidity is a confounding variable. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
11
0
5
Order By: Relevance
“…Analysing the previous studies performed about Meliponini flight activity, Silva et al (2011) noted a consensus on small bees of this group being different from the foraging activity profile of Melipona large species, in similar flight conditions. Small size species show a high surface/ volume relationship, and so their metabolism is directly related to climate variations (Oliveira, 1973; Iwama, 1977; Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Analysing the previous studies performed about Meliponini flight activity, Silva et al (2011) noted a consensus on small bees of this group being different from the foraging activity profile of Melipona large species, in similar flight conditions. Small size species show a high surface/ volume relationship, and so their metabolism is directly related to climate variations (Oliveira, 1973; Iwama, 1977; Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…Analysing the previous studies performed about Meliponini flight activity, Silva et al (2011) noted a consensus on small bees of this group being different from the foraging activity profile of Melipona large species, in similar flight conditions. Small size species show a high surface/ volume relationship, and so their metabolism is directly related to climate variations (Oliveira, 1973; Iwama, 1977; Silva et al, 2011). Indeed, temperature and relative humidity, or both, are considered as influential factors on flight activity of several stingless bees of small size, including Tetragonisca angustula (Latreille, 1811), Plebeia saiqui (Friese, 1900), Plebeia droryana (Friese, 1900), Plebeia remota (Holmberg, 1903), Plebeia emerina Friese, Trigona carbonaria (Smith, 1854), T. hyalinata (Lepeletier, 1836) and Plebeia pugnax Moure (Oliveira, 1973;Iwama, 1977;KleinertGiovannini, 1982;Imperatriz-Fonseca et al, 1985;Heard & Hendrikz, 1993;Hilário et al, 2001;Pick & Blochtein, 2002;Contrera et al, 2004).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…More than 1 / 3 of our data were recorded with RH above 90%, in the studied area. Silva et al, (2011) suggested that foragers from large species of Melipona use RH as indicator of pollen availability in the environment.…”
Section: Discussionmentioning
confidence: 99%